2019
DOI: 10.3390/genes10110842
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Quantitative Trait Loci Mapping and Expression Profiling Analysis to Identify Genes Potentially Involved in Ramie Fiber Lignin Biosynthesis

Abstract: Ramie fibers, one of the most important natural fibers in China, are mainly composed of lignin, cellulose, and hemicellulose. As the high lignin content in the fibers results in a prickly texture, the lignin content is deemed to be an important trait of the fiber quality. In this study, the genetic basis of the fiber lignin content was evaluated, resulting in the identification of five quantitative trait loci (QTLs). Three genes, whole_GLEAN_10021050, whole_GLEAN_10026962, and whole_GLEAN_10009464 that were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…However, none of these genes were confirmed to be involved in fibre development. Recent genetic studies identified some genetic loci associated with fibre traits (Chen et al, 2019;Liu et al, 2014cLiu et al, , 2017Zeng et al, 2019); however, these loci showed limited benefits for breeding improvement based on marker-assisted selection because the examined population originates from only a few parent individuals, which provided only a limited number of excellent alleles.…”
Section: Introductionmentioning
confidence: 99%
“…However, none of these genes were confirmed to be involved in fibre development. Recent genetic studies identified some genetic loci associated with fibre traits (Chen et al, 2019;Liu et al, 2014cLiu et al, , 2017Zeng et al, 2019); however, these loci showed limited benefits for breeding improvement based on marker-assisted selection because the examined population originates from only a few parent individuals, which provided only a limited number of excellent alleles.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the information on QTL mapping in ramie is negligible, which needs urgent studies to screen the population for Cd tolerance and identify the QTL to be used in the QTL pyramiding program [36,126]. Researchers have identified QTL in ramie, which were mainly related to fiber yield-related traits, lignin biosynthesis, and flowering time [126][127][128][129]. Choosing an ideal mapping population is critical in identifying dominant regions controlling Cd tolerance [125].…”
Section: Qtl Mapping For CD Tolerance In Ramiementioning
confidence: 99%
“…The rapid development of next-generation sequencing technology has recently led to the identification of large-scale single-nucleotide polymorphisms (SNPs) in ramie, resulting in several high-density genetic maps ( Liu et al, 2017 ; Zeng et al, 2019 ). Consequently, the genetic architecture of many agronomic traits, such as fiber yield, quality, and flowering time, has been systematically characterized using linkage mapping and genome-wide association mapping ( Zhu et al, 2016 ; Liu et al, 2017 ; Chen et al, 2018 , 2019 ; Zeng et al, 2019 , 2022 ; Huang et al, 2021 ; Wang et al, 2021 ), and several candidates across various loci have been documented ( Liu et al, 2017 ; Wang et al, 2021 ; Zeng et al, 2022 ). Recently, ramie feeding traits have also been researched, and the genetic basis of six forage yield-related traits was characterized, resulting in 78 significant association signals from 43 genomic regions ( Bai et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%